Nexus between Environmental Degradation and Agricultural Productivity in sub Sahara Africa; does Poverty Matters? (Global Journal of Management and Business Research, 2023)
The purpose of this study was to examine the relationships between environmental degradation and agricultural productivity in Sub-Sahara Africa over the period from 1996 to 2020. To achieve this objective, we assumed greenhouse gases as an indicator of environmental degradation, agricultural value added as an indicator of agrarian productivity, and Gross domestic product as an indicator of the poverty level. The data used in the study was collected from the World Bank Development Indicators database 2020. Concerning the estimation technique, the Pooled Mean Group estimation model was used. The results indicated that, an increase in greenhouse gas has a positive and statistically significant influence on agricultural value added in the long-run and in the short-run greenhouse gas has a negative effect on agricultural value added in Sub-Sahara Africa. It is therefore of vital essential that, various agents should encourage the use organic rather than chemical manures for agricultural production, that farm land should be equitably distributed among the farmers, and that agrarian production practices should not be done on marginal lands.
Keywords: agricultural productivity; environmental degradation; seemingly unrelated regression; sub-sahara africa and sur; poverty